2007
DOI: 10.1534/genetics.107.080622
|View full text |Cite
|
Sign up to set email alerts
|

Using Crossover Breakpoints in Recombinant Inbred Lines to Identify Quantitative Trait Loci Controlling the Global Recombination Frequency

Abstract: Recombination is a crucial component of evolution and breeding, producing new genetic combinations on which selection can act. Rates of recombination vary tremendously, not only between species but also within species and for specific chromosomal segments. In this study, by examining recombination events captured in recombinant inbred mapping populations previously created for maize, wheat, Arabidopsis, and mouse, we demonstrate that substantial variation exists for genomewide crossover rates in both outcrosse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
55
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 41 publications
4
55
1
Order By: Relevance
“…S1). Consistent with these simulations, a survey of recombination rates in five A. thaliana RIL populations at the F 8 generation, showed that the mean number of recombination events ranged from 6.23 to 8.89 per individual (37). Relative to our doubled haploid population (4.89 recombination events per individual) these RILs have undergone an additional six generations of selfing and the average number of recombination events has increased approximately twofold.…”
Section: Discussionsupporting
confidence: 69%
“…S1). Consistent with these simulations, a survey of recombination rates in five A. thaliana RIL populations at the F 8 generation, showed that the mean number of recombination events ranged from 6.23 to 8.89 per individual (37). Relative to our doubled haploid population (4.89 recombination events per individual) these RILs have undergone an additional six generations of selfing and the average number of recombination events has increased approximately twofold.…”
Section: Discussionsupporting
confidence: 69%
“…Relatedly, genetic control of recombination frequency in maize was subjected to QTL mapping by two groups, and in each study, the biggest effect QTL mapped to regions immediately adjacent to our dy mapping interval (Dole and Weber, 2007;Esch et al, 2007). These map positions were estimated to be between 166.0 and 168.5 MB (Esch et al, 2007) and at 181.1 MB (Dole and Weber, 2007) on the physical map of maize, which map just beyond our proximal and distal boundaries, respectively. Interestingly, the QTL with the greatest effect on recombination in Arabidopsis mapped near the end of chromosome 1, a region including At1G71360, predicted to encode a PM3-type SUN-domain.…”
Section: Discussionmentioning
confidence: 99%
“…Our knowledge of the genes and mechanisms involved in meiotic recombination and CO formation in plants has received a boost in the last 6 years with the use of Arabidopsis thaliana, rice (Oryza sativa), and maize (Zea mays) as model systems (Mezard et al, 2007;Mercier and Grelon, 2008). However, little is known about natural variation in recombination rates within species (Sä ll, 1990;SanchezMoran et al, 2002;Anderson et al, 2003;Esch et al, 2007;Bovill et al, 2008), which is an important issue for understanding how recombination is regulated in the wild.…”
Section: Introductionmentioning
confidence: 99%